Stress-strain state of the precast monolithic bent element - Alexandr Koyankin; Valery Mitasov (Inzhenerno-stroitelʹnyĭ zhurnal, 2020)
The features of the stress-strain state of a precast monolithic bent element (beam) arising as a result of its phased installation and loading are considered and experimentally investigated. At the first stage, the load is perceived only by the precast part of the beam made of heavy concrete, and at the second stage, monolithic lightweight concrete (expanded clay concrete) is included in the process of deformation and perception of the external load. There were two factors that served as motivation for these experimental studies: − Real precast monolithic structure, mounted on the construction site, in the absence of special structural measures (temporary mounting racks, brackets, etc.) is included in the deformation process in stages, first being the prefabricated part, followed by the monolithic one. This point is in no way reflected in the regulatory documents for design; − Insufficient study of the influence of the phased installation on the stress-strain state of the precast monolithic bent element leads to a biased assessment of its performance. Experimental studies of the stress-strain state of the precast monolithic bent element are performed, taking into account the installation process and the stepwise inclusion of the precast and then monolithic parts in the deformation process. At that, the precast part is made of heavy concrete, and monolithic-of light concrete (expanded clay concrete). The influence of the following factors on the stress-strain state of precast monolithic structures is investigated and studied: the value of pre-loading of the precast part at the first stage; the stages of installation and loading; the height of the monolithic part of the concrete. As a result of conducted research, the new data concerning features of formation of the stress-strain state of the precast monolithic element are received. The positive influence of phase loading and higher height of the monolithic part on the stress-strain state of the precast monolithic structure is revealed. In this case, the insignificant influence of the value of pre-loading of the precast part is determined.